Bio-resource Conservation and Land Use in Ethiopia - Anjulo, Agena; Chauhan, Rajesh; Hooda, M. S. (International Journal of Economic Plants, 2016)
Human are dependent on biological systems and processes for sustenance, health, well-being and enjoyment of life. Many people depend on biodiversity and other natural resources for their livelihoods. Ethiopia is one of the world’s rich biodiversity countries and it deserves attention regionally and globally. It has a very diverse set of ecosystems ranging from humid forest and extensive wetlands to the desert of the Afar depression. Ethiopia is one of the twelve known ancient countries for crop plant diversities in the world and has valuable reserves of crop genetic diversity, of which 11 cultivated crops have their centre of diversity in the country. The extensive and unique conditions in the highlands of the country have contributed to the presence of a large number of endemic species. This is due to the variation in climate, topography and vegetation. Environment Planning has focused on biodiversity conservation in response to local government interest and concern about the extensive clearing of native vegetation in Ethiopia. Ethiopia covers an area of 1,127,127 km2, of which water area covers 7,444km2 and land area 1,119,683km2, with a topographic diversity encompassing high and rugged mountains, flat-topped plateau, deep gorges with river, and rolling plains. Nearly half of the total land (41%) is non arable land, which includes forest, mountains, roads, cities, etc. and about 43% of the total land area is arable that includes temporary crop, permanent crop, pasture, and fallow land. Since the recent past, protected areas coverage is increasing in which 15% of the land is covered by national parks, wildlife sanctuaries and reserves, controlled and open hunting areas and community conservation and about 1% of land shares water surface. Biodiversity conservation and land use is a significant issue for Ethiopia and overview of the main legislation, policies and responsibilities is presented to establish biodiversity as a relevant consideration in land use planning.